PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA BENGKEL ZUL KELUARGA JAYA - Prayogie, Zai; Lie, Darwin; Butarbutar, Marisi; Simatupang, Sudung (SULTANIST: Jurnal Manajemen dan Keuangan, 2018)
The formulation of this research problem is how the influence of price and quality of service to customer satisfaction at Bengkel Zul Keluarga Jaya. The research method used in this paper is literature research and field research. The population is employees of Bengkel Zul Keluarga Jaya amounting to 30 customers. The data used are data by qualitative and qualitative data, and data collection techniques by questionnaire, interview and documentation. Then the technique of data analysis using qualitative descriptive method and quantitative descriptive method.                Results of analysis of multiple linear regression is Ŷ = 3.629 + 0.386 X1 + 0.299 X2 means there is a positive influence between price and quality of service to customer satisfaction. The strength of the relationship of the three variables is very strong, ie r = 0.826. From the coefficient of determination can be explained high low customer satisfaction 46.6%, and the remaining 53.4% explained by other factors that are not discussed in this study. From the results of processing and calculation of the questionnaire, the authors to get the conclusion that the price and quality of service applied Bengkel Zul Keluarga Jaya positive and significant impact on customer satisfaction. This is proven by hypothesis testing simultaneously, where the test result Fhitung (11,802)> Ftabel (3,35) with significance level 0,000 <alpha 0,05